Metabolome and transcriptome signatures shed light on the anti-obesity effect of Polygonatum sibiricum - Ou, Xiaobin; Wang, Xiao; Zhao, Bing; Zhao, Yi; Liu, Haiqing; Chang, Yuankai; Wang, Zhiwei; Yang, Wenqi; Zhang, Xuebin; Yu, Ke (Frontiers in Plant Science, 2023)
Abstract Obesity has become one of the major threats to human health across the globe. The rhizomes of Polygonatum sibiricum have shown promising anti-obesity effect. However, the metabolic and genetic basis mediating this beneficial effect are not fully resolved. It is well known that older rhizomes of P. sibiricum exert stronger pharmacological effects. Here, we performed high-resolution metabolome profiling of P. sibiricum rhizomes at different growth stages, and identified that three candidate anti-obesity metabolites, namely phloretin, linoleic acid and α-linolenic acid, accumulated more in adult rhizomes. To elucidate the genetic basis controlling the accumulation of these metabolites, we performed transcriptome profiling of rhizomes from juvenile and adult P. sibiricum. Through third-generation long-read sequencing, we built a high-quality transcript pool of P. sibiricum, and resolved the genetic pathways involved in the biosynthesis and metabolism of phloretin, linoleic acid and α-linolenic acid. Comparative transcriptome analysis revealed altered expression of the genetic pathways in adult rhizomes, which likely lead to higher accumulation of these candidate metabolites. Overall, we identified several metabolic and genetic signatures related to the anti-obesity effect of P. sibiricum. The metabolic and transcriptional datasets generated in this work could also facilitate future research on other beneficial effects of this medicinal plant.